KARAKTERISTIK GAYA BELAJAR MAHASISWA PGSD UAD DITINJAU DARI MODALITAS BELAJAR MAHASISWA - Muhammad Ragil Kurniawan (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Abstract:This study aims to: a) determine the distribution of student learning styles of PGSD UAD, b) determine the dominant learning styles is owned by Students PGSD UAD, c) Know the learning style that is owned by student (single or multiple). The study applied a quantitative approach specificaly survey. The data were collected through a questionnaire. The study popullation was all student PGSD UAD academic year 2013/2014. The data were descriptively analyzed. The results of the study are as follows. (1) 81% of studentshave asociallearningstyle, 51% of students have a visual and verbal leraning style, 48% of student have a solitary learning style, 47% student have a physical learning style, and 40% of student have a auditory learning style. (2) Social learning style is a type of learning style most commonly owned by students PGSD UAD. Auditory learning style is a style of learning that is at least owned by students PGSD UAD. (3) None of the students who only have one learning style.Â Keywords: leraning styles, memletics learning styles, learning modality.